Method for removing chloramphenicol in water by phosphorylated micron iron
By phosphorylation of micron iron modified zero-valent iron to remove chloramphenicol from water, the problems of low efficiency and complex process in the prior art are solved, and efficient, economical and environmentally friendly water treatment effect is achieved.
Patent Information
- Application Number
- CN202411730922.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The prior art is difficult to effectively remove chloramphenicol from water, and the traditional methods have problems such as high cost, complex process and great impact on the environment.
The zero-valent iron was modified by ball milling method using phosphorylated micron iron (P-ZVIbm) to form a material with a smaller particle size, a higher specific surface area and better dispersion, and added to the water to be treated, and the chloramphenicol was removed by stirring reaction.
It has achieved rapid and efficient removal of chloramphenicol, and has low pH limit for the reaction system, can adapt to a wide pH range, and has good industrial production adaptability and broad application prospects.
Smart Images

Figure CN119551796A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of water treatment, and in particular relates to a method for removing chloramphenicol in water by phosphated micron iron. Background Art
[0002] Chloramphenicol (CAP) is a synthetic chloronitroaromatic antibiotic. CAP is widely used in aquaculture due to its low economic cost. However, CAP cannot be completely metabolized in the body and may be excreted into the environment with feces and enter the human body through the food chain. Its toxic side effects will harm human health. At present, my country has banned the use of chloramphenicol in the aquaculture industry. However, the presence of CAP can still be detected in some aquatic products and water sources. Therefore, effective water treatment methods are urgently needed to control it.
[0003] At present, the methods for removing CAP from water bodies mainly include: adsorption method, advanced oxidation method and biological method. The adsorption method has the characteristics of simple process, low energy consumption and environmental friendliness. The most commonly used adsorbent is activated carbon, but activated carbon has other problems such as high cost and difficulty in regeneration. Advanced oxidation technology includes photocatalytic oxidation, ozone oxidation, etc., which are highly effective in degrading CAP, but this method is highly dependent on pH and may produce more toxic by-products. Biodegradation technology has low operating costs and simple processes, but the large area occupied by biological treatment, long treatment time and easy death of microorganisms limit the use of this method. Therefore, there is still a need in the field to explore a green and simple method that can achieve efficient degradation of chloramphenicol.
[0004] Zero-valent iron (ZVI) has been widely used in the field of water treatment due to its excellent reducing ability. However, ZVI also has some limitations. Its surface is very easy to passivate, which makes ZVI's utilization rate of pollutant electrons low. In order to optimize the performance of ZVI, various ZVI modification technologies have been proposed. The main modification technologies include doping ZVI with precious metals or other elements, surface modification with surfactants or polymers, embedding ZVI into carriers, and stabilizing ZVI on porous materials. At present, the application of ball milling technology in the field of ZVI is gradually gaining attention, especially in surface activation and modification. Mechanical ball milling can not only reduce the particle size of ZVI, but also peel off the oxide layer on the surface of ZVI, thereby enhancing its surface activity. In the method of modifying zero-valent iron using mechanical ball milling, researchers often add additives to ball mill with zero-valent iron to regulate the surface functional group structure of zero-valent iron, thereby enhancing the adsorption / coordination, redox, flocculation / precipitation of pollutants on the surface of zero-valent iron, and improving the efficiency of zero-valent iron in removing pollutants. The more representative additives are sulfide, oxalic acid, etc. At present, zero-valent iron modified by phosphate ball milling is a new modification method. The modified material has a smaller particle size, better dispersibility, more complete contact with pollutants in the solution, and a larger specific surface area, which makes it have a larger contact area with pollutants in the solution and more active sites for removing pollutants. In addition, the close combination of phosphate and zero-valent iron may play a synergistic role in the removal of target pollutants, which makes phosphorylated zero-valent iron more effective in removing pollutants than unmodified zero-valent iron. However, there are no relevant technical reports on the application of phosphorylated zero-valent iron to the removal of CAP in the field. Summary of the invention
[0005] The object of the present invention is to provide a phosphorylated micron iron (P-ZVI bm ) A method for removing chloramphenicol from water to achieve efficient degradation of chloramphenicol.
[0006] To achieve the above object, the technical solution of the present invention is:
[0007] A phosphorylated micronized iron (P-ZVI bm ) A method for removing chloramphenicol from water, the method comprising adding phosphorylated micron iron to water to be treated containing chloramphenicol, stirring the reaction to remove the chloramphenicol from the water.
[0008] Preferably, the preparation method of the phosphated micron iron comprises: ball milling the reduced iron powder and potassium dihydrogen phosphate to obtain the phosphated micron iron. More preferably, the molar ratio (phosphorus-iron ratio) of the potassium dihydrogen phosphate and the reduced iron powder is 1:2-1:15; more preferably, the ball-to-material ratio of the ball milling is 4.5:1; more preferably, the grinding balls of the ball milling include 3mm grinding balls and 5mm grinding balls, and the number ratio of the two is 2 (3 mm small balls): 1 (5 mm small balls); more preferably, the ball milling speed is 300-500rpm, and the ball milling time is 1-4h. The phosphated micron iron obtained by the technical scheme can be effectively applied to the removal of chloramphenicol of the present invention. The condition parameters outside the scope of the technical scheme may also be able to obtain phosphated micron iron, but the removal effect of chloramphenicol in water applied to the present invention may not be good. More preferably, the particle size of the phosphated micron iron is 100-500 mesh.
[0009] More preferably, the phosphorylated micron iron P-ZVI bm The preparation method of the material specifically includes: adding potassium dihydrogen phosphate and reduced iron powder in a molar ratio of 1:10 into a ball mill, then adding 60 grinding balls with a diameter of 3 mm and 30 grinding balls with a diameter of 5 mm, and the ball-to-material ratio is 4.5:1, placing the grinding jar in a planetary ball mill for ball milling at a speed of 500 rpm, rotating forward for 30 minutes and counterclockwise for 30 minutes as one cycle, and repeating the cycle 4 times for a total of 4 hours.
[0010] More preferably, the reduced iron powder is micron-sized, with a particle size of 100 to 500 meshes.
[0011] Preferably, the chloramphenicol CAP concentration in the water to be treated is 100-1500 μg·L -1 , more preferably 500 μg·L -1 Within the above range, it is possible to ensure the basic removal of CAP within 1 hour.
[0012] Preferably, the feeding amount of the phosphated micronized iron is not less than 0.5 g·L -1 , more preferably 0.5 to 3 g·L -1 , more preferably 1 to 3 g·L -1 .
[0013] Preferably, the pH of the reaction is 3-11, within which the CAP removal rate can be guaranteed to be higher than 99.9% after 40 minutes of reaction; more preferably, the pH is 3-9, which can ensure that the CAP removal rate is higher than 99.9% after 20 minutes of reaction.
[0014] Preferably, the reaction temperature is 20°C to 30°C, more preferably 25°C.
[0015] Preferably, the stirring rate of the reaction is 30-60 rpm, more preferably 45 rpm, and the reaction time is not less than 10 min, more preferably 10-60 min, more preferably 10-20 min.
[0016] More preferably, the reaction is carried out under anaerobic conditions.
[0017] Preferably, the reaction is carried out in an anaerobic chamber, and the chloramphenicol concentration in the water to be treated is 500 μg·L -1 The feed amount of phosphated micronized iron is 2 g·L -1 Under the conditions of pH 5, temperature 25°C, and reaction time of 20 min at a stirring rate of 45 rpm, a removal effect of 99.9% can be achieved.
[0018] Compared with the prior art, the present invention has the following beneficial effects: the present invention provides a novel and efficient method for removing chloramphenicol from water, wherein phosphorylated micronized iron P-ZVI bm It is used for the removal of organic pollutants and can quickly and efficiently remove chloramphenicol. It has low pH restrictions on the reaction system and can adapt to a wide pH range. bm It has good reducing properties and can effectively remove chloramphenicol from water. bm The preparation method is simple, suitable for industrial production, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is P-ZVI bm SEM image of .
[0020] Figure 2 It's ZVI bm and P-ZVI bm Particle size distribution diagram.
[0021] Figure 3 Commercial iron powder (ZVI), ball-milled micron iron (ZVI bm ), phosphorylated micronized iron (P-ZVI bm )Comparison of the effects of removing CAP, where [ZVI]0 = 2 g·L -1 , [ZVI bm ]0=2g·L -1 , [P-ZVI bm ]0=2g·L -1 , [CAP]0 = 500 μg·L -1 , pH=6.5, rotation speed=45rpm, P / Fe=1:10.
[0022] Figure 4 is the effect of initial CAP concentration on P-ZVIbm Remove the influence of CAP, where [P-ZVI bm ]0=2g·L -1 , pH=6.5, rotation speed=45rpm, P / Fe=1:10.
[0023] Figure 5 is the effect of the initial pH value of the solution on P-ZVI bm Remove the influence of CAP, where [P-ZVI bm ]0=2g·L -1 , [CAP]0 = 500 μg·L -1 , rotation speed = 45rpm, P / Fe = 1:10.
[0024] Figure 6 It is P-ZVI bm Effect of dosage on CAP removal, where [CAP]0 = 500 μg·L -1 , pH=6.5, rotation speed=45rpm, P / Fe=1:10.
[0025] Figure 7 Is P / Fe to P-ZVI bm Remove the influence of CAP, where [P-ZVI bm ]0=2g·L -1 , [CAP]0 = 500 μg·L -1 , pH=6.5, rotation speed=45rpm.
[0026] Figure 8 It is P-ZVI bm Comparison of CAP removal effect with S-ZVI, where [S-ZVI]0 = 2 g·L -1 , [CAP]0 = 500 μg·L -1 , pH=6.5, rotation speed=45rpm. DETAILED DESCRIPTION
[0027] In order to better clarify and understand the purpose, process scheme and advantages of the present invention, the technical scheme and implementation method of the present invention are further described clearly, completely and in detail through specific examples and in combination with the accompanying drawings. It should be noted that the embodiments described in the present invention are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operating processes are given, but they are only part of the embodiments of the present invention, not all of the embodiments. The specific implementation methods described are limited to explaining and interpreting the present invention, and do not limit the present invention. Based on the embodiments in the present invention, all other implementation methods obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0028] The experimental methods and conditions used in the following examples are conventional methods and conventional conditions unless otherwise specified. The materials, reagents or instruments used in the examples, unless otherwise specified, can be obtained from commercial sources or prepared by conventional methods. The reaction conditions embodied in the content of the invention of the present invention can achieve the reaction and obtain the product with the expected effect. Due to space limitations, some embodiments are listed below to further illustrate the advantages of the technical solution of the present invention.
[0029] Example 1
[0030] (1) Preparation of P-ZVI bm Material:
[0031] Potassium dihydrogen phosphate and reduced iron powder (reduced iron powder (99%) purchased from Shanghai McLean Biochemical Technology Co., Ltd.) were added to a ball mill at a molar ratio of 1:10, and then 60 grinding balls with a diameter of 3 mm and 30 grinding balls with a diameter of 5 mm were added, with a ball-to-material ratio of 4.5:1. The grinding jar was placed in a planetary ball mill and ball milled at a speed of 500 rpm. One cycle was forward rotation for 30 min and reverse rotation for 30 min. This cycle was repeated 4 times for a total of 4 hours. Figure 1 It is P-ZVI bm SEM image of .
[0032] (2) Test method:
[0033] This experiment was carried out in an anaerobic chamber. First, P-ZVI was weighed bm 0.08 g of the material was added to a 40 mL brown extraction bottle, and then 40 mL of oxygen-free water and a corresponding volume of CAP mother solution were added to make the initial CAP concentration in the extraction bottle 500 μg·L -1 After tightening the bottle cap, the extraction bottle was placed on a rotating incubator at 45 rpm for reaction at room temperature. The initial pH of the solution was 6.5. Samples were taken at regular intervals during the reaction, 1 mL each time, filtered through a 0.45 μm mixed cellulose filter membrane, and then injected into a liquid phase vial, and finally analyzed by high performance liquid chromatography.
[0034] P-ZVI bm The materials were replaced with commercial iron powder (ZVI), ball-milled micronized iron (ZVI bm ) and the corresponding chloramphenicol removal effect test was performed. Commercial iron powder was reduced iron powder (99%) purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; ball-milled micronized iron ZVI bm The preparation method is as follows: first, add 4 g of reduced iron powder (commercial iron powder) into a ball mill, then add 60 grinding balls with a diameter of 3 mm and 30 grinding balls with a diameter of 5 mm, place the ball mill into a planetary ball mill and perform ball milling at a speed of 500 rpm, with forward rotation for 30 min and reverse rotation for 30 min as one cycle, repeat 4 times for a total of 4 hours. Figure 2 It's ZVI bm and P-ZVI bm Table 1 is the particle size distribution diagram of ZVI bm and P-ZVI bm Summary table of specific surface area, pore volume and average pore diameter.
[0035] Table 1 ZVI bm and P-ZVI bm Summary of specific surface area (BET), pore volume and average pore diameter (BJH)
[0036]
[0037] Test results see Figure 3 As shown, Figure 3 Commercial iron powder (ZVI), ball-milled micronized iron (ZVI bm ), phosphorylated micronized iron (P-ZVI bm )Comparison of the effects of removing CAP. It can be seen that ZVI, ZVI bm 、P-ZVI bm The dosage is 2g·L -1 , the initial concentration of CAP was 500 μg·L -1 After 1 h of reaction, the removal rate of CAP by ZVI was 5.7%. bm The removal rate of CAP was 5.6%, P-ZVI bm The removal rate of CAP can reach 99.9% in 20 minutes. bm Compared with P-ZVI bm The removal effect of CAP is significantly improved beyond expectations.
[0038] Example 2
[0039] The P-ZVI prepared in Example 1 was used bm Materials. This experiment was carried out in an anaerobic chamber. First, P-ZVI was weighed bm 0.08 g of the material was added to a 40 mL brown extraction bottle, and then 40 mL of oxygen-free water and the corresponding volume of CAP solution were added to make the initial concentrations of 100, 300, 500, 1000, and 1500 μg·L -1 After tightening the bottle cap, the extraction bottle was placed on a rotating incubator at 45 rpm for reaction at room temperature. The initial pH of the solution was 6.5. Samples were taken regularly during the reaction, 1 mL each time, filtered through a 0.45 μm mixed cellulose filter membrane, and then injected into a liquid phase vial, and finally analyzed by high performance liquid chromatography.
[0040] Test results see Figure 4 As shown, Figure 4is the effect of initial CAP concentration on P-ZVI bm Effect of CAP removal. It can be seen that with the increase of the initial CAP concentration, the removal rate of CAP by the material gradually decreases. However, when the initial CAP concentration is 100-1500 μg·L -1 Within this range, it can be guaranteed that CAP is basically removed within 1 hour.
[0041] Example 3
[0042] The P-ZVI prepared in Example 1 was used bm Materials. This experiment was carried out in an anaerobic chamber. First, P-ZVI was weighed bm Add 0.08g of the material into a 40mL brown extraction bottle, add 40mL of oxygen-free water, and use 1mol·L -1 HCl or NaOH was used to adjust the pH of the solution to 3, 5, 7, 9, or 11, and then the corresponding volume of CAP solution was added to make the initial concentration 500 μg·L -1 After tightening the bottle cap, the extraction bottle was placed on a rotating incubator at a speed of 45 rpm for reaction at room temperature. During the reaction, samples were taken regularly, 1 mL each time, filtered through a 0.45 μm mixed cellulose filter membrane, and then injected into a liquid phase vial, and finally analyzed by high performance liquid chromatography.
[0043] Test results see Figure 5 As shown, Figure 5 The initial pH value of the solution affects the P-ZVI bm Effect of removing CAP. It can be seen that in the range of pH = 3 to 11, the material can achieve a CAP removal rate of 99.9% within 1 hour. As the pH increases, the CAP removal rate of the material decreases. In the range of pH = 3 to 9, the CAP removal rate can be guaranteed to be higher than 99.9% when the reaction is 20 minutes, and in the range of pH = 3 to 11, the CAP removal rate can be guaranteed to be higher than 99.9% when the reaction is 40 minutes.
[0044] Example 4
[0045] The P-ZVI prepared in Example 1 was used bm Materials. This experiment was carried out in an anaerobic chamber. P-ZVI bm 0.02, 0.04, 0.08, and 0.12 g of the material were added to a 40 mL brown extraction bottle, and then 40 mL of oxygen-free water and the corresponding volume of CAP solution were added to make the initial concentration 500 μg·L -1 After tightening the bottle cap, the extraction bottle was placed on a rotating incubator at 45 rpm for reaction at room temperature. The initial pH of the solution was 6.5. Samples were taken at regular intervals during the reaction, 1 mL each time, filtered through a 0.45 μm mixed cellulose filter membrane, and then injected into a liquid phase vial, and finally analyzed by high performance liquid chromatography.
[0046] Test results see Figure 6 As shown, Figure 6 For P-ZVI bm Effect of dosage on P-ZVI bm Remove the influence of CAP. It can be seen that when the dosage is 0.5~3g·L -1 The CAP removal rate can be guaranteed to be higher than 90% within 1 hour. With the increase of the dosage, the CAP removal rate of the material gradually increases. When the material dosage is 2g·L -1 and 3g·L -1 When the reaction time is 20 min, the removal rate of CAP is higher than 99.9%.
[0047] Example 5
[0048] Phosphorylated micron-iron with phosphorus-iron ratios of 1:2, 1:5, 1:15, 1:20 and 1:100 were prepared based on the method for preparing phosphorylated micron-iron in Example 1. This experiment was carried out in an anaerobic chamber. First, P-ZVI with different phosphorus-iron ratios were weighed. bm 0.08 g of each material was added to a 40 mL brown extraction bottle, and then 40 mL of oxygen-free water and a corresponding volume of CAP mother solution were added to make the initial CAP concentration in the extraction bottle 500 μg·L -1 After tightening the bottle cap, the extraction bottle was placed on a rotating incubator at 45 rpm for reaction at room temperature. The initial pH of the solution was 6.5. Samples were taken at regular intervals during the reaction, 1 mL each time, filtered through a 0.45 μm mixed cellulose filter membrane, and then injected into a liquid phase vial, and finally analyzed by high performance liquid chromatography.
[0049] Test results see Figure 7 As shown, Figure 7 The figure shows the removal effect of CAP by phosphorylated micron iron with different phosphorus to iron ratios. It can be seen that the removal effect of CAP by phosphorylated micron iron with different phosphorus to iron ratios is different. Among them, the removal effect of CAP is best in the range of P / Fe of 1:2 to 1:15, and the removal rate of CAP within 20 minutes is higher than 99.9%. P-ZVI with P / Fe of 1:20 and 1:100 bm P-ZVI with P / Fe in the range of 1:2 to 1:15 bm In comparison, the removal rate of CAP decreased significantly.
[0050] Comparative Example 1
[0051] Preparation method of sulfide micron zero-valent iron (S-ZVI): (1) Acid washing: In an anaerobic glove box, use deionized water treated with deoxygenation to prepare a concentration of 50 mmol·L -1Take 20 mL of dilute hydrochloric acid and add it to a 40 mL extraction bottle. Then add 5.6 g of commercial micronized zero-valent iron. Shake well and let it stand for 1 hour to remove the iron oxide on the surface. (2) Sulfurization: Add 20 mL and 10 mL of 0.5 mol·L -1 Na2S solution was added to obtain S-ZVI with sulfur-iron ratios of 1:10 and 1:20. After being placed in a rotary incubator for 12 hours of rotational mixing, the mixture was filtered. (3) Drying: The filtered solid was freeze-dried (12 hours) to obtain dry S-ZVI powders with different sulfurization ratios.
[0052] This experiment was carried out in an anaerobic chamber. First, 0.08 g of S-ZVI with different sulfur-iron ratios were weighed and added to 40 mL brown extraction bottles. Then, 40 mL of oxygen-free water and the corresponding volume of CAP mother solution were added to make the initial CAP concentration in the extraction bottle 500 μg·L -1 After tightening the bottle cap, the extraction bottle was placed on a rotating incubator at 45 rpm for reaction at room temperature. The initial pH of the solution was 6.5. Samples were taken at regular intervals during the reaction, 1 mL each time, filtered through a 0.45 μm mixed cellulose filter membrane, and then injected into a liquid phase vial, and finally analyzed by high performance liquid chromatography.
[0053] Test results see Figure 8 As shown, Figure 8 For P-ZVI bm Comparison of CAP removal effect with S-ZVI. bm Compared with the system, S-ZVI has a poorer removal effect on CAP. After 20 minutes of reaction, P-ZVI bm CAP was basically degraded completely, while the removal rates of CAP by S-ZVI with S / Fe ratio of 1:10 and 1:20 were only 45.9% and 70.6%. After 60 minutes of reaction, the removal rates of CAP by S-ZVI with S / Fe ratio of 1:10 and 1:20 were only 83.3% and 95.6%. It can be seen that phosphorylated micron iron has an excellent effect on the removal of chloramphenicol.
[0054] The above-described embodiments are only preferred solutions of the present invention and are not intended to limit the present invention in any form. Other variations and modifications are possible without exceeding the technical solutions described in the claims.
Claims
1. A method for removing chloramphenicol from water by phosphorylated micron iron, characterized in that: The method comprises the following steps: adding phosphorylated micron iron to water to be treated containing chloramphenicol, stirring the water for reaction and removing the chloramphenicol from the water.
2. A method for removing chloramphenicol from water by phosphorylated micron iron according to claim 1, characterized in that: The preparation method of the phosphated micron iron comprises: ball milling reduced iron powder and potassium dihydrogen phosphate to obtain the phosphated micron iron, wherein the molar ratio of the potassium dihydrogen phosphate to the reduced iron powder is 1:2 to 1:
15.
3. A method for removing chloramphenicol from water by phosphorylated micron iron according to claim 2, characterized in that: The ball-to-material ratio of the ball mill is 4.5:1; the grinding balls of the ball mill include 3mm grinding balls and 5mm grinding balls, and the ratio of the number of the two is 2:
1.
4. A method for removing chloramphenicol from water by phosphorylated micron iron according to claim 2, characterized in that: The ball milling speed is 300-500 rpm, and the ball milling time is 1-4 h.
5. A method for removing chloramphenicol from water by phosphorylated micron iron according to claim 1, characterized in that: The preparation method of phosphated micron iron specifically comprises: adding potassium dihydrogen phosphate and reduced iron powder in a molar ratio of 1:10 into a ball mill, then adding 60 grinding balls with a diameter of 3 mm and 30 grinding balls with a diameter of 5 mm, with a ball-to-material ratio of 4.5:1, placing the grinding jar into a planetary ball mill for ball milling at a speed of 500 rpm, rotating forward for 30 minutes and reverse for 30 minutes as one cycle, repeating 4 times for a total of 4 hours.
6. A method for removing chloramphenicol from water by phosphorylated micron iron according to claim 1, characterized in that: The chloramphenicol CAP concentration in the water to be treated is 100-1500 μg·L -1 .
7. A method for removing chloramphenicol from water by phosphorylated micron iron according to claim 1, characterized in that: The feeding amount of the phosphated micron iron is not less than 0.5 g·L -1 .
8. A method for removing chloramphenicol from water by phosphorylated micron iron according to claim 1, characterized in that: The pH of the reaction is 3-11.
9. A method for removing chloramphenicol from water by phosphorylated micron iron according to claim 1, characterized in that: The pH of the reaction is 3-9.
10. The method for removing chloramphenicol from water by phosphorylated micron iron according to claim 1, characterized in that: The stirring rate of the reaction is 30-60 rpm, and the reaction time is not less than 10 min.
Citation Information
Patent Citations
Phosphorized chitosan loaded magnetic nano-iron composite material as well as preparation method and application thereof
CN114733491A
Phosphorus-doped zero-valent iron modified material, preparation method thereof and method for efficiently reducing and removing pollutants by using phosphorus-doped zero-valent iron modified material
CN115784412A
Phosphating modified zero-valent iron material as well as preparation method and application thereof
CN116550972A
Nanometer zero-valent iron surface phosphating treatment process for removing various pollutants in industrial wastewater
CN117699941A